Waiving chronic fish tests: possible use of acute-to-chronic relationships and interspecies correlations. Issue 7 (14th September 2017) - Kienzler, Aude; Halder, Marlies; Worth, Andrew
ABSTRACT: EU chemicals legislation requires the use of all available information for hazard and risk assessment before new tests on vertebrates are proposed or conducted. In this context, extrapolation approaches for avoiding chronic fish testing on the basis of existing data have been explored. Simple linear relationships and interspecies sensitivity ratios between Daphnia and fish were calculated and acute-to-chronic relationships and ratios were calculated for fish, taking into consideration the mode of action. The best fitted relationships for the prediction of chronic fish toxicity are obtained based on acute fish and Daphnia data. Chemicals acting by unspecific reactivity and non-polar narcosis give the strongest acute and chronic Daphnia -to-chronic fish relationship. With acute fish data, strong relationships are obtained for all mode of action. Daphnia was found to be more sensitive than fish to several aniline derivatives and pesticides acting through cholinesterase inhibition, and less sensitive than fish to known endocrine disruptors. Extreme (i.e. <1 or >100) interspecies sensitivity ratios were mainly evident for chemicals acting by polar narcosis and specific reactivity. The safety factor of 100 commonly applied in environmental risk assessment does not seem to be equally protective for each mode of action.